2019
DOI: 10.1029/2019ja026619
|View full text |Cite
|
Sign up to set email alerts
|

Proton Temperature Anisotropies in the Plasma Environment of Venus

Abstract: Velocity distribution functions (VDFs) are a key to understanding the interplay between particles and waves in a plasma. Any deviation from an isotropic Maxwellian distribution may be unstable and result in wave generation. Using data from the ion mass spectrometer IMA (Ion Mass Analyzer) and the magnetometer (MAG) onboard Venus Express, we study proton distributions in the plasma environment of Venus. We focus on the temperature anisotropy, that is, the ratio between the proton temperature perpendicular (T⊥) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(37 citation statements)
references
References 76 publications
3
31
0
Order By: Relevance
“…Which of the two instabilities will grow is dependent on the plasma-β (the ratio between plasma and magnetic pressure). For small β, for instance, in the solar wind, the IC instability dominates (Hellinger et al 2006;Matteini et al 2007;Bale et al 2009;Woodham et al 2018Woodham et al , 2019, whereas for high β, for instance, behind the bow shock, the MM instability plays a major role (Volwerk et al 2008a(Volwerk et al ,b, 2016Fränz et al 2017;Bader et al 2019).…”
Section: High-frequency Magnetic Fluctuationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Which of the two instabilities will grow is dependent on the plasma-β (the ratio between plasma and magnetic pressure). For small β, for instance, in the solar wind, the IC instability dominates (Hellinger et al 2006;Matteini et al 2007;Bale et al 2009;Woodham et al 2018Woodham et al , 2019, whereas for high β, for instance, behind the bow shock, the MM instability plays a major role (Volwerk et al 2008a(Volwerk et al ,b, 2016Fränz et al 2017;Bader et al 2019).…”
Section: High-frequency Magnetic Fluctuationsmentioning
confidence: 99%
“…It was also shown that behind the bow shock the MM instability criterion was not at all, or only marginally, fulfilled. We estimate the solar wind plasma-β with B SW = 8 nT, N SW = 20 cm −3 and use a typical value of T i,SW = 13 eV (Bader et al 2019):…”
Section: Around the Bow Shockmentioning
confidence: 99%
“…However we did not investigate the matter further. The following plots for solar minimum are not those from Bader et al (2019), but rather the results of our new implementation of the fitting methodology. However, the two sets of results for that period show good agreement.…”
Section: Resultsmentioning
confidence: 99%
“…The values in this table are calculated using all successful fits. If we remove fits using the additional criteria suggested by Bader et al (2019) listed in Section 3, the parameter values and uncertainties in the solar wind and both magnetosheath regions do not change significantly. This is consistent with the low probability density of measurements below the instrument's limit for reliability in these regions.…”
Section: Comparative Histograms For Regions Of Interestmentioning
confidence: 99%
“…Downstream of the bow shock, two different situations can be met depending on the orientation of the interplanetary magnetic field with respect to the shock normal: a quasi-perpendicular or a quasi-parallel bow shock. In the case of the quasi-perpendicular bow shock it is expected that downstream ion temperature anisotropy will develop, which can trigger various ion-scale instabilities such as mirror modes (Volwerk et al 2008a(Volwerk et al ,b, 2016Bader et al 2019). These waves have been observed beyond Venus's terminator and they can either be generated locally or are transported by the plasma flow in the magnetosheath (Sahraoui et al 2003).…”
Section: Induced Magnetosphere and Plasma Environmentmentioning
confidence: 99%